1996
DOI: 10.1073/pnas.93.18.9881
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential target genes for the neuron-restrictive silencer factor.

Abstract: The neuron-restrictive silencer factor (NRSF) represses transcription of several neuronal genes in nonneuronal cells by binding to a 21-bp element called the neuron-restrictive silencer element (NRSE). We have performed data base searches with a composite NRSE to identify additional candidate NRSF target genes. Twenty-two more genes, 17 of which are expressed mainly in neurons, were found to contain NRSE-like sequences. Many of these putative NRSEs bound NRSF in vitro and repressed transcription in vivo. Most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
341
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(356 citation statements)
references
References 39 publications
13
341
1
1
Order By: Relevance
“…The 21 bp human RE-1 sequences associated to these genes were compared with those of consensus RE-1 and of the known CX36 RE-1 [11]. All sequences, except that of MUNC18-1, were closely homologous to the consensus one and displayed a typical core [23] consisting of two invariant domains (Fig. 5a).…”
Section: Resultsmentioning
confidence: 99%
“…The 21 bp human RE-1 sequences associated to these genes were compared with those of consensus RE-1 and of the known CX36 RE-1 [11]. All sequences, except that of MUNC18-1, were closely homologous to the consensus one and displayed a typical core [23] consisting of two invariant domains (Fig. 5a).…”
Section: Resultsmentioning
confidence: 99%
“…NRSF\REST is known to be a 116 kDa protein [133] containing eight non-canonical zinc fingers [132], only one of which has been shown to be crucial for repression of the type II sodium channel gene [134]. Interestingly, several research groups have now identified NRSE-directed silencer activity in a variety of neuronal as well as non-neuronal genes [130][131][132][135][136][137][138][139][140][141].…”
Section: Nrsf/nrsementioning
confidence: 99%
“…The NRSF is a repressor of a large number of neuronal terminal differentiation genes in non-neuronal tissues as well as neuronal stem cells reviewed in references. 24,[35][36][37][38][39][40] Studies with the neuronal n(AchR) b-2 subunit revealed a dual regulatory role of the NRSE. In transgenic mice, the NRSE functioned as either a repressor or enhancer depending on the cellular context in the neurons.…”
Section: Discussionmentioning
confidence: 99%